The Agency of Things in Medieval and Early Modern Art Materials, Power and Manipulation - Jurkowlaniec, Grażyna; Matyjaszkiewicz, Ika; Sarnecka, Zuzanna (Taylor & Francis, 2017)
This volume explores the late medieval and early modern periods from the perspective of objects. While the agency of things has been studied in anthropology and archaeology, it is an innovative approach for art historical investigations. Each contributor takes as a point of departure active things: objects that were collected, exchanged, held in hand, carried on a body, assembled, cared for or pawned. Through a series of case studies set in various geographic locations, this volume examines a rich variety of systems throughout Europe and beyond.